Insights into interfacial effect and local lithium-ion transport in polycrystalline cathodes of solid-state batteries - Shuaifeng Lou (Nature Portfolio, 2020)
Solid state battery is regarded as one of the most promising next generation energy storage systems due to high safety and high energy density. Here, authors demonstrate the importance of interfacial local environment in polycrystalline cathodes for electrochemical reactions in solid-state batteries.